STANDARDIZATION OF TRAILOKYASUNDAR RASA WITH SPECIAL REFERENCE TO RASARATNASAMUCHCHAYA - Golecha, *Paras Dilipkumar; D, Pargunde Sheela; Kurve, Siddhisha Nirmalkumar; Punde, Ashish Arun (International Journal of Ayurveda and Pharma Research, 2016)
The imperishable fundamentals of Ayurveda, which were laid down by the great sages of the olden days are still applicable because of their eternal sustainability. These fundamentals need to be time tested through scientific research not only to prove the validity but also to update the existing knowledge. Rasa Shastra, with its blend of mystical and medical insights, is source of valuable knowledge. Rasa aushadhis are appreciated for their Quick efficacy even at small dosages, long durability etc. Trailokyasundar rasa is a Rasakalpa explained in Rasaratnasamucchaya. Little research has been done on this Kalpa and it is not commonly prescribed by the Ayurvedic practitioners and Vaidyas. Considering all the above factors, a step has been taken to develop standard operating procedures (SOP) for preparing Trailokyasundar rasa, in this study. This is an attempt towards standardizing the processes at every stage of preparation of Trailokyasundar rasa (so as to define the SMP) which is exclusively mentioned in Rasaratnasamuchhaya Pandurogadhikara. The final product has been analyzed on the basis of various parameters such as organoleptic characters, physico- chemical properties and XRF testing. The observations recorded through these techniques show that following the classically recommended directions for this Kalpa, results in the final product matching the desired standards.